NURSING EXPERIENCES AND DEFENSIVE STRATEGIES REGARDING CARE IN THE INTENSIVE CARE UNIT - Aline de Oliveira Moreira; Hérica de Araújo Sousa; Jairo Antônio Ribeiro (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976927207 Objective: to identify experiences and defensive strategies in the Intensive Care Unit nursing team. Method: qualitative research, descriptive, that used the content thematic analysis when analyzing data. It was performed with eight nurses from the Adult and Mixed Pediatric Intensive Care Unit in a great general hospital in the south of Minas Gerais. The data collection occurred between July and August 2012, by means of semistructured interviews. Results: the data was gathered into three categories: Caring satisfaction in Intensive Care, Care frustration in the Intensive Care, and Coping with daily situations: defense mechanisms. Conclusions: the nurses take pleasure in working in the intensive care, in spite of under appreciation being present. The caretaker´s feelings should be valued, because this interferes directly with the given assistance and life quality of the Intensive Care Nurse.